Studi Kinetika dan Isoterm Adsorpsi Ion Logam Berat Cr(VI) pada Arang Aktif - Dinda Novia Rahayu Putri; Hilman Imadul Umam; Teguh Pambudi (P3M Politeknik Negeri Jember, 2026)
Heavy metal pollution in aquatic systems has become an increasingly significant environmental issue alongside the expansion of industrial activities. Effluents generated from electroplating, leather tanning, metal finishing, and pigment production industries often contain various hazardous heavy metals that pose serious threats to both the environment and human health. One of the heavy metals frequently detected in industrial wastewater is hexavalent chromium (Cr(VI)), which exhibits high toxicity and considerable mobility in aquatic enviroments. This study aimed to evaluate the effectiveness of activated carbon as an adsorbent for the removal of Cr(VI) ions from aqueous solutions using a batch adsorption method. Operational parameters analyzed included solution pH, adsorbent dosage, and contact time. Chromium concentrations were determined using a UV-Vis spectrophotometer, while the adsorption mechanism was investigated through kinetic and isotherm models. The results indicated that adsorption efficiency increased significantly under acidic conditions, reaching an optimum at pH 2 with an adsorbent dosage of 0.25 g and a contact time of 60 minutes. Kinetic analysis revealed that the adsorption process followed a pseudo-second-order model, suggesting the involvement of chemical interactions between the metal ions and the adsorbent surface. Isotherm analysis demonstrated that the Langmuir model provided a better fit than the Freundlich model, indicating that adsorption occurred in a monolayer configuration on the adsorbent surface. These findings suggest that activated carbon has high potential as an adsorbent material for treating wastewater containing heavy metals, particularly hexavalent chromium.